APLP2 Regulates Refractive Error and Myopia Development in Mice and Humans. - Andrei V Tkatchenko; Tatiana V Tkatchenko; Jeremy A Guggenheim; Virginie J M Verhoeven; Pirro G Hysi; Robert Wojciechowski; Pawan Kumar Singh; Ashok Kumar; Gopal Thinakaran; Consortium for Refractive Error and Myopia (CREAM); Cathy Williams (PLoS Genetics)
Myopia is the most common vision disorder and the leading cause of visual impairment worldwide. However, gene variants identified to date explain less than 10% of the variance in refractive error, leaving the majority of heritability unexplained ("missing heritability"). Previously, we reported that expression of APLP2 was strongly associated with myopia in a primate model. Here, we found that low-frequency variants near the 5'-end of APLP2 were associated with refractive error in a prospective UK birth cohort (n = 3,819 children; top SNP rs188663068, p = 5.0 × 10-4) and a CREAM consortium panel (n = 45,756 adults; top SNP rs7127037, p = 6.6 × 10-3). These variants showed evidence of differential effect on childhood longitudinal refractive error trajectories depending on time spent reading (gene x time spent reading x age interaction, p = 4.0 × 10-3). Furthermore, Aplp2 knockout mice developed high degrees of hyperopia (+11.5 ± 2.2 D, p < 1.0 × 10-4) compared to both heterozygous (-0.8 ± 2.0 D, p < 1.0 × 10-4) and wild-type (+0.3 ± 2.2 D, p < 1.0 × 10-4) littermates and exhibited a dose-dependent reduction in susceptibility to environmentally induced myopia (F(2, 33) = 191.0, p < 1.0 × 10-4). This phenotype was associated with reduced contrast sensitivity (F(12, 120) = 3.6, p = 1.5 × 10-4) and changes in the electrophysiological properties of retinal amacrine cells, which expressed Aplp2. This work identifies APLP2 as one of the "missing" myopia genes, demonstrating the importance of a low-frequency gene variant in the development of human myopia. It also demonstrates an important role for APLP2 in refractive development in mice and humans, suggesting a high level of evolutionary conservation of the signaling pathways underlying refractive eye development.